Analisis Yuridis Tentang Sengketa Pemilu Terhadap Pelaksanaan Sistem Informasi Rekapitulasi (SIREKAP) Yang Terindikasi ‘Defect’ Pada Pemilu Tahun 2024 Yang Berpotensi Merugikan Bakal Calon Presiden - Akhsan Firly Saetriyan; Intan Syahrani; Melisa Nurdiana; Muhamad Rizal Fauzan; Novira Putri Rustandi; Salwa Yurisha (Demokrasi: Jurnal Riset Ilmu Hukum, Sosial dan Politik, 2024)
The Recapitulation Information System, known as SIREKAP, launched by the General Election Commission of the Republic of Indonesia, is an election tool based on the latest technology to receive and manage manual vote counting of general election results which are converted into digital data. The Recapitulation Information System (SIREKAP) is the starting point in the process of transitioning election administration from manual to digital, which will ensure that elections in Indonesia can be held effectively and efficiently in the future, so that elections and democracy will look better. Through SIREKAP, this long process can be shortened, costs can be reduced, disputes can be extended and resolved more quickly, and elections can be conducted in a more environmentally friendly manner. However, this has many challenges and risks that must be taken seriously. SIREKAP is also vulnerable to election data security problems due to system hacking or data manipulation which could endanger the integrity of election results, especially in the 2024 General Election for Presidential and Vice Presidential Candidates.